PENGARUH CSR TERHADAP KINERJA KEUANGAN PERUSAHAAN DAN EMPLOYEE TURNOVER (Studi Empiris pada Perusahaan-perusahaan yang Mengungkapkan Laporan Keberlanjutan menggunakan Kerangka GRI dan Terdaftar di BEI Tahun 2020-2022) - Sapria, Septo Allan Toto; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
The purpose of this study is to investigate the impact of CSR on corporate financial performance and employee turnover. Moreover, this study seeks to explore and compare the impact of CSR measured through two sources, namely internal CSR reports and external index. The dependent variables in this study are corporate financial performance and employee turnover, while the independent variable in this study is CSR. Firm size, firm leverage, and gender diversity are also used as control variables in this study.The study uses secondary data in the form of corporate sustainability reports obtained from the Bloomberg Terminal. Using a purposive sampling method, the sample obtained was 85, which are companies that disclose sustainability reports using the GRI framework and are listed on the Indonesia Stock Exchange in 2020-2022. The study also uses multiple regression analysis.The results of this study shows that CSR has a positive impact on corporate financial performance and a negative impact on employee turnover. However, the significance of these impacts is only seen in CSR measured based on internal CSR reports, not from CSR measured based on external index.